Coexistence of Ankylosing Spondylitis With Morphea: A Case Report - Kevser GÜMÜŞSU; Aylin REZVANİ and Özlem SU and Nihal ÖZARAS and Mustafa GÜLER (Archives of Rheumatology, 2014)
Morphea, which is also known as localized scleroderma, is a disorder caused by excessive collagen deposition and characterized by the thickening and hardening of the skin. Unlike systemic sclerosis, morphea lacks features such as Raynaud phenomenon, joint involvement, sclerodactyly, and constitutional symptoms. It may be associated with drug use and is occasionally found together with other autoimmune diseases. In this article, we report a 60-year-old woman who was admitted to our outpatient clinic due to HLA B27 + ankylosing spondylitis with axial involvement and morphea. Her disease was able to be managed with exercise and non-steroidal antiinflammatory drugs, however, a 10¥7 cm diameter atrophic lesion of medium hardness was identified on her left shoulder. The histopathology of the lesion was compatible with morphea, and improved with topical steroid treatment. Although the concomitance of autoimmune diseases is frequent, there is no coexistence of morphea with ankylosing spondylitis in the literature, except a case who was considered to be associated with the adalimumab use. Despite limited data, however, common autoimmune pathogenesis may be seen in association with ankylosing spondylitis and morphea.